Virtual consent and the use of electronic informed consent form in clinical research in Brazil - Silva,Juliana Carvalho Rocha Alves da (2021)
SUMMARY OBJECTIVE: In view of the need to apply term free and informed consent (IC) in clinical research involving humans, in accordance with the Brazilian ethical standards (CNS Resolution No. 466/2012), it is necessary to assess whether this practice is being effective and can be improved. The aim of this study was to evaluate the use of the IC in electronic format (e-IC), regarding its feasibility and suitability, as a complement to the written/physical consent form. METHODS: Quantitative-qualitative research with a questionnaire instrument. RESULTS: Greater retention of information and fewer wrong answers were observed after the application of the e-IC. CONCLUSIONS: The use of e-IC is of great value to research participants in Brazil.